Analisis Pemilihan Moda Transportasi Pribadi Terhadap Angkutan Umum Mikrotrans Jaklingko Di Wilayah Tanjung Priok - Aisyah Ummi Syarifah; Siti Sahara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research aims to analyze the choice of private transportation modes of Tanjung Priok residents compared to public transportation, Mitro Trans Jaklingko. Tanjung Priok is an area with high population density and serious traffic congestion problems. This research tries to find out what factors influence the people of Tanjung Priok in choosing to use private vehicles such as cars or motorbikes compared to public transportation, Mitro Trans Jaklingko. This method uses a population survey method with a structured questionnaire to collect data from respondents who are potential users of both modes of transportation. The factors analyzed include the quality of Mitro Trans Jaklingko services. It is hoped that the results of this research will provide further insight into transportation preferences in Tanjung Priok and provide appropriate policy recommendations for the government and transportation service providers to increase the use of public transportation and reduce traffic congestion.